Politik Identitas Dan Politisasi Agama Dalam Konteks Pemilu - Ferdian Nugraha; Erik Pikri Setiadi; Tatsa Hasby Rahima; Andi Septiadi (Jurnal Sosial Politik dan Hukum, 2024)
This study examines the phenomenon and impact of identity politics and religious politics in the context of elections. The main question asked is how these two phenomena contribute to democracy. The purpose of this study is to understand how identity politics affects the democratic process and how religious politics is used in political strategy. Using a quantitative research methodology, this research involves observation, interviews, document analysis and group discussions. The results of the study show that identity and religion politics have a significant impact on the electoral process and are often used to undermine trust in the democratic system by exploiting public sentiment, and even potentially polarizing society. The findings show that the majority of respondents believe that identity politics has a significant impact on their choices in life. Public pragmatism and lack of political education are the causes of this phenomenon. The discussion explained that the crisis of public trust in the political system and its participants, social and economic vulnerabilities, and the influence of political elites on public opinion through the media and propaganda negatively undermine democracy. Therefore, special measures, such as inclusive political education, are needed to increase public trust and uphold democratic integrity. The research contributes by providing information on the challenges of democracy and, moreover, by offering a framework for inclusive policies that reduce the influence of identity politics and religious politics.